Consumer Behavior in Decision Making - What Are the Factors? - Sadiku, Kosovare Mustafa; Mjaku, Gentiana; Qarri , Albert (International Journal of Membrane Science and Technology, 2023)
It is challenging for businesses that operate in the market to flourish without a grasp of the requirements and habits of the consumer. Sociodemographic, cultural, and psychological factors have an impact on consumer buying behavior and the brands of goods they choose to use and consume. Most of the locally produced goods were just known by their offering name and not by their brand. Delivery of these things has improved over time. The infrastructure of product sales units has undergone significant alteration today. This study’s goals are to examine customer behavior in the selection of food brands, as well as the influence of the consumer’s sociodemographic and psychological traits. The Republic of Kosovo’s citizens provided the study’s data. These data are processed using statistical techniques such as utilizing an econometric model through multiple regression analysis to determine which socio-demographic and psychological aspects influence decision-making, using SPSS application software version 26.0. These data were gathered as a function of the study questions. The results of the analysis show that all the variables taken in the study affect the choice of food brands but from the highest impact to the least are as follows: They have the most impact the Revenue with 181%, then we have gender with 150%. Starting with a confidence level of 95% and with a high level of significance, this result is followed by the ranking with the Educational Level with 145%, it is thought that people who have a level of educational achievement are more aware of the quality of the product, the origin of him than people who do not have high educational development. Then it is followed by Age 112% and Profession 89%.